Estudo da influência dos parâmetros operacionais na eletrodeposição de camadas eletrocatalíticas de ligas de Ni-Fe. - Sousa, Josenir Barreto de (2007)
The present work shows the study of the ultrasound irradiation influence in the electrodeposition of Ni-Fe coatings. The electrocatalytic performance of these coatings for the hydrogen evolution reaction (her) in alkaline medium was also evaluated. The Ni-Fe coatings were obtained from plating solutions containing 0.06 mol.dm-3 Ni2SO4.6H2O, 0.48 mol.dm-3 Na3C3H5O7.2H2O, 0.71 mol.dm-3 Na2CO3 and 0.16 mol.dm-3 (bath 1) and 0.04 mol.dm-3 FeSO4.7H2O (bath 2). It was also added 8.4 mL L-1 H2SO4 to maintain the pH below 1. The electrodepositions were carried out under galvanostatic control in the range of 10 mA cm-2 to 50 mA cm-2, at room temperature (≈ 28ºC) and at 55ºC in the presence and in the absence of ultrasound irradiation. All coatings were deposited on disk mild steel substrate with an exposed geometric area of 0.7 cm2. The hydrogen evolution reaction was studied in 0.5 mol.dm-3 NaOH. In all electrochemical experiments Pt was the auxiliary electrode and Hg/HgO, OH- (0,5 mol.dm-3) was the reference one. The coatings ware characterized by scanning electron microscopy (SEM), cyclic voltammetry (CV) and the electrocatalytic properties of the Ni-Fe coating were evaluated by Tafel polarization and long-term performance tests. The results showed that the use of the ultrasound irradiation leads to an increase of the Fe content in the electrodeposits. Additionally, the coatings obtained in presence of ultrasound also present the best performance for her.